Proposing Cloud Based Intrusion Detection System for Tracing Intruder Attacks - Chaturvedi, AK; Lone, FA (International Journal of Computer Sciences and Engineering, 2025)
Before proposing a new model and implementing it in the Intrusion Detection Systems, First find out how intrusion detection is performed on Software as a Service (SaaS), Platform as a Service (PaaS) and Infrastructure as a Service (IaaS) offerings, along with the available host, network and hypervisor-based intrusion detection options. The ability to perform intrusion detection in the cloud is heavily dependent on the model of cloud computing. In cloud computing, most of the attacks till today traced are the remote attacks. In this paper, we are proposing a model for Cloud Based Intruder Detection System [CBIDS]. This model is created for tracing the attacks on the online storage at SaaS and PaaS layer of cloud computing and appropriately the recommended action will be taken to protect the stored data and executing the handler accordingly. Further modifications in this model will be done on the basis of obtaining requirements and gaps in tracing the attacks.